Penerapan konsep community based tourism (CBT) di desa wisata candirejo borobudur mewujudkan kemandirian desa - Ahsani, Retno Dewi Pramodia; Suyaningsih, Oktavia; Ma’rifah, Nur; Aerani, Elsa (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
This study aims to examine about the impact of application of the concept of Community Based Tourism (CBT) in realizing the independence of Candirejo village. The research method used is qualitative method. The results of this study are Candirejo Village Management Manager is a Cooperative whose entrepreneurs are the original community of Candirejo Village, The impact of CBT concept implementation can be seen through economic aspects (job diversification, improvement of housing condition and new business development), social (social interaction, community participation, change of mindset), cultural adoption, and environment (improvement of public facilities). With the fulfillment of Indicator Independence of the village is not entirely Candirejo village can be releasedÂ of the government aid funds, but at least in the fulfillment of basic needs, community activities, construction of public facilities, and economic activities available can be fulfilled independently